Use and misuse of prescription stimulants by university students: a cross-sectional survey in the french-speaking community of Belgium, 2018 - Martine Sabbe; Javier Sawchik; Mégane Gräfe; Françoise Wuillaume; Sara De Bruyn; Pierre Van Antwerpen; Guido Van Hal; Martin Desseilles; Jamila Hamdani; Hugues Malonne (BMC, 2022)
Abstract Background Misuse of prescription stimulants (PS) has been reported among students to enhance academic performance in Flanders (Belgium). However, PS misuse among students in the French-speaking community is unknown. The main purpose of the study was to estimate the prevalence of medical use and misuse of PS by university students in the French-speaking community (Belgium), and to investigate the reasons and sources associated with PS misuse. Methods A cross-sectional online survey was performed in 2018. All university students 18 years and older were invited to participate and asked about PS use, including medical (i.e., used for therapeutic purposes) and nonmedical reasons and sources of PS. Results In total, 12 144 students participated in the survey (median age = 21 years, 65.5% female). The estimated prevalence of PS use was 6.9% (ever use) and 5.5% (past-year). Among ever users, 34.7% were classified as medical users and 65.3% as misusers. Lifetime prevalence of misuse was estimated at 4.5%. The most common reason for medical use was treatment of attention disorder (85.9%). Reasons for misuse were mainly to improve concentration (76.1%) or to stay awake and study longer (50.7%). Friends or acquaintances inside the student community and general practitioners were the main sources of PS for misuse (41.5% and 23.5%, respectively). Conclusions This study found that rates of misuse of PS in French-speaking universities in Belgium were in line with studies conducted in Flanders and Europe. Academic institutions can use these results to tailor their drug prevention campaigns.